Implementation evaluation of the universal primary education policy at Khomasdal Primary School and Gammams Primary School in the Khomas Region, Namibia - Uusiku, Victoria Jakula (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPA)--Stellenbosch University, 2019.